The Role of Print and Electronic Media in the Defense of Human Rights: A Jordanian Perspective - Aldamen, Yasmin (Jordan Journal of Social Sciences, 2017)
The doctrine of human rights has gained increasing attention and respectability around the world. Electronic and print media can also play their roles by highlighting the violations of human rights, raising awareness, and influencing legislations and resolutions. This study is an attempt at throwing light on this role of media in the context of Jordan. The researcher selected a random sample of (1243) people,18 years of age and above, of the (5.1) million people, the total population of Jordan according to the general census carried out by Population and Housing Census at the Department of Statistics (DoS) in October 2004. Findings showed significant differences in the role of print and electronic media. The role of electronic media was found to be better than that of print media. Jordanian media can improve its performance by having greater freedom and by focusing on the uses and gratification of recipients. The study found out that; it is very important to train journalists and increase their awareness more about the laws of human rights which leads to enhance the role of media in addressing human rights issues, and there is a need to increase dedication to human rights issues individually and collectively. In addition to, encourage more studies and field researches on the role of media in the defense of in human rights in Jordan.